Effects of rainfall on the use of emergency medical services - Ishak San; Semih Korkut; Eren Usul; Afsin Emre Kayipmaz (Medicine Science, 2020)
Emergency Medical Services (EMS) is an essential component of any healthcare system in the world, providing patients with medical care and a transfer system to hospitals. This system requires for an undisrupted and flawless provision of healthcare, considering factors that are controllable and uncontrollable. The aim of this study is to determine the effects of precipitation on the use of emergency medical services. This is a retrospective observational study, for which the precipitation data used was obtained from the Turkish State Meteorological Service. The daily number of cases transferred by EMS teams was obtained from the ASOS system of the Ankara Directorate of Emergency Medical Services. Data from 2002 days were included in the study. There were 198,816 cases on non-rainy days, while the total number of cases on rainy days was 94,407. While the median of the daily number of cases of non-rainy days was 140 (45), this value was 148 (49) for rainy days. There was a statistically significant difference between the two groups in terms of daily number of cases (p [Med-Science 2020; 9(3.000): 688-91]